Hydrothermal carbon functional material for separating phenolic acids and / or saccharides as well as preparation and application of hydrothermal carbon functional material

By using hydrothermal carbon functional materials in traditional Chinese medicine as the stationary phase of the chromatographic column, the problem of separation of oligosaccharides in traditional Chinese medicine was solved, and efficient separation of phenolic acids and oligosaccharides was achieved, and the research and drug development of traditional Chinese medicine was promoted.

CN119470751APending Publication Date: 2025-02-18SHANXI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411558289.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively isolate and purify oligosaccharides in traditional Chinese medicine, especially those in Morinda, which hinders the progress of oligosaccharide structure-effect research.

Method used

Monodispersed carbon spheres are prepared by hydrothermal method using biomass such as glucose, maltose or cyclodextrin, and taurine and amino acids are bonded simultaneously on the basis of this to form a hydrothermal carbon functional material as the stationary phase of the chromatographic column, and through optimization The use of polar fillers and buffer salts enables the separation of phenolic acids and oligosaccharides.

Benefits of technology

The efficient separation of phenolic acids and oligosaccharides in traditional Chinese medicine has been achieved, which proves the universality of this method and is applicable to the preparation of oligosaccharides in different traditional Chinese medicines, and has promoted the basic research and drug development of traditional Chinese medicine oligosaccharides.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470751A_ABST
    Figure CN119470751A_ABST
Patent Text Reader

Abstract

The invention provides a method for separating and analyzing phenolic acid compounds and saccharides. The method comprises the following steps: firstly, preparing a benzoic acid and saccharide mixed sample, and then preparing different biomass hydrothermal carbon chromatographic columns with an HILIC mode and taurine bonded hydrothermal carbon, taurine and amino acid simultaneously bonded biomass hydrothermal carbon chromatographic columns. A separation analysis experiment is carried out on phenolic acid and oligosaccharide by adopting an acetonitrile / water mobile phase and combining ultraviolet and evaporative light detectors. According to the method, benzoic acid and carbohydrates can be analyzed firstly, and the established method has different separation selectivity from other hydrophilic chromatographic columns and is suitable for separation of a traditional Chinese medicine complex system. And a basis is provided for explaining pharmacodynamic substance research of the traditional Chinese medicine oligosaccharide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sample pretreatment and separation preparation of Chinese medicine extracts. The present invention can be used for the separation and analysis of phenolic acids and sugars, laying a foundation for clarifying the structure-activity relationship of Chinese medicine oligosaccharides. Specifically, monodisperse carbon spheres are prepared using glucose, maltose, and β-cyclodextrin as carbon sources, and taurine and amino acid functional materials are bonded on this basis. The prepared stationary phase can be applied to the field of separation and preparation of phenolic acids and oligosaccharide components in Chinese medicines such as Morinda officinalis and foods. Background Art

[0002] The separation and purification of Chinese medicine oligosaccharides are the key links in oligosaccharide structure analysis and efficacy research. The high complexity of oligosaccharides themselves in composition, connection, derivatization, micro-heterogeneity, etc. makes the study of Chinese medicine oligosaccharides a difficult problem that plagues Chinese medicine scientists. Morinda officinalis is the dried root of Morinda officinalis, a plant of the Rubiaceae family. It tastes sweet and spicy and belongs to the kidney meridian and liver meridian. It has the effects of tonifying kidney yang, strengthening tendons and bones, and removing rheumatism. It is used for impotence and spermatorrhea, uterine cold and infertility, irregular menstruation, rheumatism and arthritis. Studies have shown that Morinda officinalis mainly contains chemical components such as polysaccharides, oligosaccharides, iridoid glycosides and anthraquinones. The sugar content in Morinda officinalis is relatively high. The 2020 edition of the Chinese Pharmacopoeia uses the content of oligosaccharide component nesitose as the quality standard for evaluating Morinda officinalis medicinal materials. Studies have found that oligosaccharide components have anti-anxiety, anti-aging, anti-inflammatory, promote sperm production and resist myocardial ischemia-reperfusion. However, the structure of Morinda officinalis oligosaccharides is complex, the molecules contain a large number of hydroxyl groups, the chemical properties are similar, and they have complex characteristics such as multiple branches, multiple connection methods, derivatization, and diverse stereochemistry, which restricts the separation of Morinda officinalis oligosaccharides. At present, there is no better method to separate oligosaccharides, which in turn hinders the structure-activity study of Morinda officinalis oligosaccharides.

[0003] Hydrothermal carbon materials are new functional materials prepared by hydrothermal reaction of sugars or carbon-containing organic matter. With water as the reaction medium, it has attracted widespread attention due to its easy modification, strong hydrophilicity, and green environmental protection. Hydrothermal carbon materials use sugars and other materials as raw materials in a reactor, and undergo a series of chemical reactions such as dehydration, cracking, cyclocondensation, etc. at a certain temperature and pressure to form colloidal carbon materials. It can be used as a carrier of metallic lithium, a catalyst carrier, etc., and hydrothermal carbon balls are easy to be modified by surface chemical reactions. At present, hydrothermal carbon materials have been used for the enrichment of polar compounds such as nucleosides, ionic compounds, phosphorylated peptides (DOI: 10.1039 / C8GC03706J) and glycosylated peptides (DOI: 10.1021 / ACSSUSCHEMENG.9B01382).

[0004] Taking all these factors into consideration, the development of a new type of chromatographic stationary phase material for the enrichment and separation of benzoic acid compounds and oligosaccharides in traditional Chinese medicine will not only promote basic research on natural oligosaccharides in aqueous extracts of traditional Chinese medicine, but also facilitate the scale-up of the preparation of oligosaccharide monomers and the development of oligosaccharide drugs, showing excellent economic value. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing and applying a hydrothermal carbon functional material for separating phenolic acids and sugars and simultaneously bonding taurine and amino acids. Biomass hydrothermal carbon stationary phases such as glucose and cyclodextrin are used, and then a functional material simultaneously bonding taurine and amino acids is prepared as a chromatographic column stationary phase. By using ultraviolet and evaporative light detectors, isocratic elution can achieve better separation of oligosaccharides. By optimizing the functional groups on the surface of the polar filler, adding buffer salts, optimizing their concentration and pH, the separation of representative phenolic acid compounds and representative oligosaccharides can be achieved, proving that this method has universal applicability and will be applicable to the preparation of oligosaccharides in different traditional Chinese medicines.

[0006] The present invention relates to the preparation and application of hydrothermal carbon functional materials including phenolic acids and sugar separation, including a method for quickly and easily preparing monodisperse carbon-coated silica, that is, a one-step hydrothermal method is adopted, with glucose or maltose or cyclodextrin as the carbon source, PVP (polyvinyl pyrrolidone), NVP (N-vinyl pyrrolidone) and other cross-linking agents are added, water is used as the reaction medium, and 4-5μm silica is used as the substrate to successfully prepare monodisperse carbon spheres with controllable particle size and morphology. Based on the polyhydroxy characteristics of the hydrothermal carbon layer of the carbohydrate, the epoxy groups are modified, and taurine and its analog amino acids are simultaneously bonded to the hydrothermal carbon spheres by the epoxy ring-opening reaction. It can be seen from the experimental results that the pore size and pore volume of the synthesized hydrothermal carbon and the hydrothermal carbon stationary phase bonded with taurine and aspartic acid are slightly reduced, which proves that the material was successfully prepared. Figure 2 , Figure 3 , Figure 4 It can be seen that the material of the present invention improves the separation performance of phenolic acid substances and sugar substances when used as a chromatographic stationary phase, and has advantages over the comparative amide chromatographic stationary phase. The reaction conditions are mild, green and environmentally friendly, and suitable for separation and amplification of preparation of Chinese medicine oligosaccharides.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] (1) Dissolve an appropriate amount of glucose or maltose or cyclodextrin in a certain amount of water to reach 0.01-1 g / mL, add an appropriate amount of 0.1-5 g of NVP, transfer to a reactor containing a polytetrafluoroethylene liner, heat and dissolve to form a transparent solution.

[0009] (2) Add a certain amount of 1-10g of 3-5um silica to a reactor containing a polytetrafluoroethylene liner and react in an oven at 160-190 degrees for 6-8 hours.

[0010] (3) After a period of reaction, the reactor is taken out of the oven and cooled, the obtained biomass hydrothermal carbon material is washed with water and ethanol and filtered, and finally the obtained product is dried in an oven to obtain monodisperse carbon microspheres.

[0011] (4) The dried monodisperse carbon microspheres are placed in a glass or polytetrafluoroethylene reaction container, and an epoxy coupling agent is added dropwise to react at a certain temperature. The obtained product is washed and filtered with methanol, water, etc., and dried in an oven to obtain epoxy hydrothermal carbon spheres.

[0012] (5) Take 3 g of dried epoxy hydrothermal carbon modified silica and dissolve it in alkaline carbonate buffer, add 0.1-2 g of taurine and its analog molecules or amino acids, heat the reaction for a certain period of time, filter, wash, add a certain amount of amino acids, wash with methanol, water, and methanol, and dry the obtained solid in an oven to obtain a taurine and amino acid simultaneously bonded stationary phase.

[0013] As a preferred method, the concentration of the glucose aqueous solution, maltose aqueous solution, and cyclodextrin aqueous solution is 50 mg / mL to 200 mg / mL.

[0014] As a preferred method, the silica matrix added during the hydrothermal reaction preferably has a particle size of 3-7 microns and a pore size of 8-100 nanometers.

[0015] The specific steps include:

[0016] (1) Prepared different biomass hydrothermal carbon modified silica materials: the silica particle size range is 2-5 μm, and the different biomass is one or more of glucose, maltose, or cyclodextrin;

[0017] (2) Then, the carbon material is post-modified. The post-modification refers to using epichlorohydrin reagent to prepare taurine and amino acid through amino-epoxy ring-opening reaction on the basis of microspheres and simultaneously bonding hydrothermal carbon fillers. The schematic structural formula is as follows: The silica microspheres shown are wrapped by hydrothermal carbon fillers;

[0018]

[0019] As a preferred method, 1-7 g of epoxy coupling agent including epichlorohydrin, glycidyl methacrylate and other crosslinking agents can be added during the hydrothermal reaction, the temperature is preferably 40-80° C., and the time is preferably 6-24 hours.

[0020] As a preferred method, the dried epoxy hydrothermal carbon microspheres are dispersed in a carbonate buffer solution (pH=7-10), and the amount of mixed solvent required for each gram of epoxy hydrothermal carbon modified silica is 5-50 mL.

[0021] The present invention has the following advantages:

[0022] 1. High selectivity. The present invention proposes a method of using a glucose hydrothermal carbon hydrophilic matrix chromatographic column and bonding taurine and simultaneously bonding taurine and amino acid functional material chromatographic columns based on the glucose hydrothermal carbon hydrophilic matrix chromatographic column, which has excellent selectivity for separating benzoic acid compounds.

[0023] 2. The preparation process is simple and easy to expand production. Taurine, which is easy to bond, is added first, and then amino acids such as cysteine ​​or aspartic acid, which are difficult to bond, are added to prepare functional materials that simultaneously bond taurine and amino acids, which are suitable for separating and preparing different types of phenolic acids and oligosaccharides.

[0024] 3. Wide application range. Compared with the method of directly bonding taurine or amino acid on the surface of silica, the chromatographic column of hydrothermal carbon functional material bonded with taurine and amino acid in the present invention generates epoxy groups through residual hydroxyl groups and epichlorohydrin derived from glucose, and then forms epoxy rings with taurine, amino acid and polyamino compounds. The synthesis is green and simple, the hydrophilicity is strong, the silicon hydroxyl groups can be better shielded, and the benzene ring interaction and π-π interaction of the hydrothermal carbon layer can also be utilized. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0026] Figure 1 This is the separation result of representative phenol, benzoic acid and caffeic acid substances of the products of Example 1 and Comparative Examples 4 and 5;

[0027] Figure 2 The results of separation of representative phenol, benzoic acid and caffeic acid substances by the products of comparative examples 1, 2, 3 and 5 are shown below: 1. toluene; 2. phenol; 3. 1-naphthol; 4. p-hydroxybenzoic acid; 5. caffeic acid;

[0028] Figure 3 The results of separation of some monosaccharide and disaccharide isomers of the products of Examples 1, 2, 3, and 4 are shown;

[0029] Among them: 1. Fructose 2. Glucose 3. Sucrose 4. Maltose 5. Lactose

[0030] Figure 4 , the result of separation of the product of Example 2 on the mixed solution of oligosaccharides from Morinda officinalis of traditional Chinese medicine;

[0031] Figure 5 Comparative Example 4 product separation result diagram of the traditional Chinese medicine Morinda officinalis oligosaccharide mixture; DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with examples and comparative examples. The examples are only intended to illustrate the present invention, but not to limit the present invention.

[0033] Embodiment 1:

[0034] Weigh 12g of cyclodextrin in a reactor with a polytetrafluoroethylene liner, add 2g of PVP and 100mL of deionized water, and place in an oven at 100°C for 30 minutes. After the solution is clarified, add 4g of silica (particle size 4um, average pore size 9nm), stir evenly, react in an oven at 200°C for 6 hours, take out the reactor, cool to room temperature, wash the material with deionized water and ethanol 5 times each until the supernatant is transparent, and place the solid material in an oven at 80°C for 6 hours to obtain cyclodextrin hydrothermal carbon microspheres.

[0035] Take 2.3g of the above cyclodextrin hydrothermal carbon microspheres in a three-necked flask, add 7mL of epichlorohydrin (0.089mol), 10mL of DMSO, and then add 2mL of 0.1mol / mL ammonium carbonate and ammonium bicarbonate buffer solution to adjust the pH to 10, put it in a water bath and stir at 70℃ for 6 hours. The obtained solid was washed with methanol, water, and methanol twice each, and vacuum dried in an oven at 80℃ for 6 hours to obtain epoxy-modified hydrothermal carbon material. The pore size data shows that the average pore size (8.1nm) is smaller than that of silica (9.3nm). The particle size is about 4.2 microns;

[0036] Take 2.3g of the above-mentioned epoxy-modified hydrothermal carbon material into a three-necked flask, add 20mL 0.1mol / mL disodium hydrogen phosphate solution and 2.0g taurine (0.016mol), stir and react at 65°C in a water bath for 12 hours, then add 9.7g aspartic acid (0.073mol), react for 6 hours, and finally wash with methanol, water, and methanol three times respectively, and vacuum dry in an oven at 80°C for 6 hours to obtain taurine and aspartic acid simultaneously bonded to cyclodextrin hydrothermal carbon material, the particle size of which is 4.3 microns as analyzed by scanning electron microscopy.

[0037] The average pore size (8.4nm) is smaller than that of silica (9nm). Then the column was filled to conduct comparative tests on samples including phenol, benzoic acid compounds, monosaccharide, disaccharide isomer mixture, etc. The separation results were better than those of taurine bonded hydrothermal carbon alone and different biomass hydrothermal carbon coated silica stationary phase.

[0038] Embodiment 2:

[0039] Weigh 12g of cyclodextrin in a reactor with a polytetrafluoroethylene liner, add 2g of PVP and 100mL of deionized water, and place in an oven at 100°C for 30 minutes. After the solution is clarified, add 4g of silica (particle size 4um, average pore size 9nm), stir evenly, react in an oven at 200°C for 6 hours, take out the reactor, cool to room temperature, wash the material with deionized water and ethanol 5 times each until the supernatant is transparent, and place the solid material in an oven at 80°C for 6 hours to obtain cyclodextrin hydrothermal carbon microspheres.

[0040] Take 2.3g of the above cyclodextrin hydrothermal carbon microspheres in a three-necked flask, add 3.5mL epichlorohydrin (0.045mol), 10mL DMSO, and then add 2mL 0.1mol / mL sodium carbonate and sodium bicarbonate buffer solution to adjust pH 10, put it in a water bath at 60℃ and stir for 6 hours. The obtained solid was washed with methanol, water, and methanol twice each, and vacuum dried in an oven at 80℃ for 6 hours to obtain epoxy-modified hydrothermal carbon material. Its pore size (8.3nm) is smaller than that of silica (9nm). The particle size is about 4.2 microns.

[0041] Take 2.3g of the above epoxy-modified hydrothermal carbon material in a three-necked flask, add 20mL 0.1mol / mL disodium hydrogen phosphate solution, 2g taurine (0.016mol), stir and react at 65℃ in a water bath for 12 hours, then add 2.13g aspartic acid (0.016mol), react for 6 hours, finally wash with methanol, water, and methanol three times respectively, and dry in an oven at 80℃ under vacuum for 6 hours to obtain taurine and aspartic acid simultaneously bonded to cyclodextrin hydrothermal carbon material, the particle size of which is 4.2 microns after SEM analysis. The pore size and specific surface area data show that the average pore size (8nm) is smaller than that of silica (9nm).

[0042] The product of Example 2 was used to pack the chromatographic column to analyze and test the traditional Chinese medicine Morinda officinalis oligosaccharide mixture, which can achieve the separation of complex samples and has better separation effect than a single bonded stationary phase.

[0043] Example 3: Similar to Example 1 (process and conditions are the same as Example 1), except that aspartic acid is replaced with an equal molar amount of cysteine.

[0044] The product was then filled into a chromatographic column for comparative testing of samples including phenol, benzoic acid compounds, monosaccharide and disaccharide isomer mixtures, etc.; the separation results were better than those of different biomass hydrothermal carbon-coated silica stationary phases and taurine-bonded hydrothermal carbon stationary phases alone, and the separation results were similar to those in Example 1.

[0045] Example 4: Similar to Example 2 (process and conditions are the same as Example 2), except that aspartic acid is replaced with an equal molar amount of cysteine.

[0046] Then the product was filled into a chromatographic column for comparative testing of samples including phenol, benzoic acid compounds, monosaccharide and disaccharide isomer mixtures, etc.; the separation results were better than those of taurine-bonded hydrothermal carbon alone and different biomass hydrothermal carbon-coated silica stationary phases, and the separation results were similar to those in Example 1.

[0047] Example 5: Similar to Example 1 (process and conditions are the same as Example 1), except that cyclodextrin is replaced with an equal mass of maltose.

[0048] Then the product was filled into a chromatographic column for comparative testing of samples including phenol, benzoic acid compounds, monosaccharide and disaccharide isomer mixtures, etc.; the separation results were better than those of taurine-bonded hydrothermal carbon alone and different biomass hydrothermal carbon-coated silica stationary phases, and the separation results were similar to those in Example 1.

[0049] Example 6: Similar to Example 1 (process and conditions are the same as Example 1), except that cyclodextrin is replaced with an equal mass of glucose.

[0050] Then the product was filled into a chromatographic column for comparative testing of samples including phenol, benzoic acid compounds, monosaccharide and disaccharide isomer mixtures, etc.; the separation results were better than those of taurine-bonded hydrothermal carbon alone and different biomass hydrothermal carbon-coated silica stationary phases, and the separation results were similar to those in Example 1.

[0051] Comparative Example 1:

[0052] Weigh 8g of cyclodextrin into a reactor containing a polytetrafluoroethylene liner, add 4g of PVP and 80mL of deionized water, and place it in an oven at 80°C for 30 minutes. After the solution is clarified, add 4g of silica and stir evenly. After reacting in an oven at 180°C for 5 hours, take out the reactor, cool to room temperature, wash the material with deionized water and ethanol 5 times until the supernatant is transparent, and place the solid material in an oven at 80°C for vacuum drying for 6 hours to obtain cyclodextrin hydrothermal carbon microspheres.

[0053] The pore size and specific surface area data were tested, and the average pore size (8.06nm) was smaller than that of silica (9.25nm). Scanning electron microscopy showed that the particle size was 4.3 microns. Then, the chromatographic column was filled to test samples including phenol, benzoic acid compounds, monosaccharide, disaccharide isomer mixture, etc.

[0054] Comparative Example 2:

[0055] Weigh 4g of maltose into a reactor with a polytetrafluoroethylene liner, add 4g of NVP and 80ml of deionized water, and place it in an oven at 80°C for 30 minutes. After the solution is clarified, add 4g of silica and stir evenly. After reacting in an oven at 200°C for 4 hours, take out the reactor, cool to room temperature, wash the material with deionized water and ethanol 5 times until the supernatant is transparent, and place the solid material in an oven at 80°C for 6 hours to obtain maltose hydrothermal carbon microspheres.

[0056] The pore size and specific surface area data show that the pore size (8.9nm) is smaller than that of silica (9.25nm). Scanning electron microscopy observation shows that the particle size is about 4.3 microns, and then the chromatographic column is filled to compare and test samples including phenol benzoic acid compounds, monosaccharide and disaccharide isomer mixtures, etc.

[0057] Comparative Example 3:

[0058] Weigh 4g of glucose into a reactor with a polytetrafluoroethylene liner, add 4g of PVP and 80ml of deionized water, and place in an oven at 80°C for 30 minutes. After the solution is clarified, add 4g of silica, stir evenly, and react in an oven at 200°C for 4 hours, then take out the reactor, cool to room temperature, wash the material with deionized water and ethanol 5 times until the supernatant is transparent, and place the solid material in an oven at 80°C for 6 hours in a vacuum dryer to obtain glucose hydrothermal carbon microspheres.

[0059] The data of pore size and specific surface area show that the pore size (8.3nm) is smaller than that of silica (9.25nm). Scanning electron microscopy characterization shows that the particle size is 4.3 microns, and then the chromatographic column is filled to compare and test samples including phenol benzoic acid compounds, monosaccharide and disaccharide isomer mixtures, etc.;

[0060] Comparative Example 4:

[0061] Weigh 8g of cyclodextrin into a reactor with a polytetrafluoroethylene liner, add 4g of PVP and 80mL of deionized water, and place in an oven at 80°C for 30 minutes. After the solution is clarified, add 4g of silica, stir evenly, and react in an oven at 180°C for 5 hours, then take out the reactor, cool to room temperature, wash the material with deionized water and ethanol 5 times until the supernatant is transparent, and place the solid material in an oven at 80°C for 6 hours in a vacuum dryer to obtain cyclodextrin hydrothermal carbon microspheres.

[0062] Take 2g of the above microspheres in a three-necked flask, add 7mL of epichlorohydrin (0.089mol) and then add 2mL of 0.1mol / mL sodium bicarbonate solution to adjust the pH to 10, put it in a water bath at 50℃ and stir for 4 hours. The obtained solid was washed with methanol, water, and methanol several times, and dried in an oven at 80℃ under vacuum for 6 hours to obtain the epoxy-modified hydrothermal carbon material.

[0063] Take 2g of the above epoxy-modified hydrothermal carbon material in a three-necked flask, add 15mL 0.1mol / mL sodium carbonate solution and 4g taurine (0.032mol), stir and react at 65℃ in a water bath for 12 hours, and finally wash with methanol, water and methanol three times respectively, and vacuum dry in an oven at 80℃ for 6 hours to obtain taurine-bonded cyclodextrin hydrothermal carbon material. Scanning electron microscopy characterization shows that the particle size is 4.3 microns. The pore size and specific surface area data test show that the pore size (8.1nm) is smaller than that of silica (9.25nm), and the specific surface area is also reduced compared to before coating. To prove the successful preparation of the new material, the chromatographic column was filled to compare the performance of samples including phenol, benzoic acid mixture, monosaccharide, disaccharide isomer mixture, etc.;

[0064] Comparative Example 5:

[0065] A commercial hydrophilic chromatography column with a particle size of 4 microns, an amide column (Supersil HILIC 100A, 5um, ID4.6 mm*150mm) was purchased from the market, and the separation was performed using the same liquid chromatography conditions as in the example, including phenol benzoic acid compounds, monosaccharide, disaccharide isomer mixture and other samples for comparative testing; the test conditions were the same.

[0066] Comparative Example 6:

[0067] Similar to Comparative Example 4 (process and conditions are the same as Comparative Example 4), the difference is that taurine is replaced by an equal molar amount of cysteine.

[0068] Then the product was filled into a chromatographic column for comparative testing of samples including phenol, benzoic acid compounds, monosaccharide, disaccharide isomer mixtures, etc.; the separation results were similar to those of comparative example 4 taurine-bonded hydrothermal carbon.

[0069] Figure 1 , Figure 2 : Graph showing the experimental results of separation of phenols and phenolic acid compounds.

[0070] Experimental conditions: Analytes and their concentrations in the same aqueous solution: (1) toluene (3 mg / mL); (2) phenol (2 mg / mL); (3) 1-naphthol (1 mg / mL); (4) p-hydroxybenzoic acid (0.5 mg / mL); (5) caffeic acid (0.7 mg / mL); Chromatographic conditions: column effective length and inner diameter: 150 mm × 4.6 mm id; mobile phase: ACN / Water, v / v, 88 / 12; buffer salt (containing 50 mM ammonium formate) was added to the mobile phase water; injection volume: 5 uL, flow rate: 1 mL / min, detection wavelength: 254 nm.

[0071] It can be concluded that the retention time of caffeic acid in the glucose hydrothermal carbon chromatographic column is the longest and the peak shape is better, while the comparative commercial hydrophilic amide chromatographic column does not achieve effective separation.

[0072] Figure 3 : Standard sugar compound separation results diagram.

[0073] Separated samples and their concentrations in the same aqueous solution: monosaccharides, disaccharides, trisaccharides, and tetrasaccharides: (1) fructose (1.2 mg / mL), (2) glucose (6 mg / mL), (3) sucrose (6 mg / mL), (4) maltose (10 mg / mL), (5) lactose (5 mg / mL). Chromatographic conditions: effective column length and inner diameter: 150 mm × 4.6 mm id; mobile phase: acetonitrile-water buffer solution (containing 50 mM ammonium formate) / (80:20, v / v), flow rate: 1 mL / min. Detector: evaporative light scattering, tube temperature: 50°C.

[0074] It can be seen that the taurine of the present invention is bonded to the hydrothermal carbon column with aspartic acid or PEI at the same time and the separation result is better. The separation result of the simultaneous bonding to the hydrothermal carbon (f curve) and the commercial amide column (d curve) is better. On the two columns, the retention time of disaccharides is enhanced, and there is no elution under the same chromatographic method conditions of 30 minutes. Moreover, the material of taurine and aspartic acid or polyethyleneimine bonded to the hydrothermal carbon at the same time has the highest separation degree of glucose and fructose, so the effect of the present invention is better.

[0075] Figure 4 , Figure 5 : Graph showing the separation effect of complex samples on the chromatographic columns (150 mm × 4.6 mm id) filled with the products of Example 2 and Comparative Example 4.

[0076] Separation sample: aqueous solution of Morinda officinalis oligosaccharide mixture (about 1 mg / mL); chromatographic conditions: mobile phase: A-water (20 mM ammonium acetate), B-acetonitrile; linear gradient elution 0-30 min, 25%-50% A, 75%-50% B (V / V); flow rate: 1 ml / min. Detector: evaporative light detector, drift tube temperature: 50°C. It can be seen that the taurine and aspartic acid simultaneously bonded hydrothermal carbon column of the present invention has a good peak shape and a good result in the initial separation.

Claims

1. A method for preparing a hydrothermal carbon functional material for separating phenolic acids and / or sugars, characterized in that: (1) using silicon dioxide as a core, preparing a hydrothermal carbon modification layer on its surface; (2) then performing post-modification of the carbon material to prepare a hydrothermal carbon filler bonded with taurine and amino acid at the same time; the molar ratio of taurine to amino acid is 1:1-1:8, preferably 1:1-1:2; The amino acid may be one or more of aspartic acid, cysteine, and lysine.

2. The preparation method according to claim 1, characterized in that: The specific steps include: (1) Prepared different biomass hydrothermal carbon modified silica materials: the silica particle size range is 2-5 μm, and the different biomass is one or more of glucose, maltose, or cyclodextrin; (2) Then, the carbon material is post-modified. The post-modification refers to using epichlorohydrin reagent to prepare taurine and amino acid through amino-epoxy ring-opening reaction on the basis of microspheres and simultaneously bonding hydrothermal carbon fillers. The schematic structural formula is as follows: The silica microspheres shown are wrapped by hydrothermal carbon fillers; 3. The preparation method according to claim 2, characterized in that: In synthesizing the biomass hydrothermal carbon modified silica material, the type of maltose can be one or two of α-maltose and β-maltose; the type of cyclodextrin can be one or more of α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin.

4. The preparation method according to claim 1 or 2, characterized in that: The type of taurine can be one or more of taurine and its analogs; The taurine and amino acid bonded hydrothermal carbon are hydrothermal carbon microspheres in which both are modified to the epoxy group at the same time, and the bonding process is that taurine and amino acid are bonded sequentially.

5. The preparation method according to claim 1, 2 or 4, characterized in that: Preparation process of epoxy hydrothermal carbon: take 2.3g of the above cyclodextrin hydrothermal carbon microspheres in a three-necked flask, add 1-7mL epichlorohydrin (0.013-0.089mol), 10-15mL DMSO and then add 2-2.5mL 0.1-0.15mol / mL carbonate buffer solution to adjust pH 9-10, put it in a water bath at 60-70℃ and stir for 4-12 hours; wash the obtained solid with methanol, water and methanol respectively 1-5 times, and dry it in an oven at 60-90℃ under vacuum for 2-12 hours to obtain epoxy-modified hydrothermal carbon material; the molar amount of epoxy groups on the surface of each gram of epoxy hydrothermal carbon is 0.006mol~0.035mol; The specific process of hydrothermal carbon bonding taurine and amino acid stationary phase is as follows: adding the epoxy hydrothermal carbon obtained above to a mixed solvent of water and alcohol in a volume ratio of 10:1-1:10, the amount of mixed solvent required for each gram of epoxy hydrothermal carbon is 3-50 mL, taurine is 0.11-2.23 g, and reacting at 40-70° C. for 5-20 hours; after centrifugation and washing, adding amino acids and reacting for 2-10 hours, the molar number of taurine is 5-20% (preferably 1 0%-20%); the molar number of the amino acid is 5-80% (preferably 10%-80%) of the molar number of the epoxy groups on the hydrothermal carbon surface, that is, the molar ratio of taurine to amino acid is 1:1-1:8, preferably 1:1-1:2; washing with methanol and water for 2-5 times respectively, and drying the obtained solid at 60-100° C. for 6-48 hours to obtain a hydrothermal carbon stationary phase in which taurine and amino acid are simultaneously bonded, and the bonding amount ranges from 0.001 mol to 0.035 mol per gram of epoxy group hydrothermal carbon.

6. A preparation method and application as claimed in any one of claims 1 to 5, comprising simultaneously bonding the prepared taurine and amino acids to a hydrothermal carbon filler and separating a mixture of phenolic acids or sugars.

7. A preparation method and application as claimed in claim 6, comprising simultaneously bonding the prepared taurine and amino acids to a hydrothermal carbon filler and separating a mixture of phenolic acids or sugars.

8. The hydrothermal carbon filler with taurine and amino acid bonded simultaneously as claimed in claim 7 has the advantage of being used in the analysis of mixtures of traditional Chinese medicine extracts.

9. The use according to claim 8, characterized in that: A chromatographic column with an inner diameter of 4-20 mm is prepared by a homogenization method, and separation analysis and preparation are carried out in combination with ultraviolet and evaporative light scattering detectors; for example, one or two of taurine and aspartic acid bonded hydrothermal carbon columns, taurine and cysteine ​​bonded hydrothermal carbon columns, etc. are used to separate and analyze the component.

10. The use according to claim 7, characterized in that: Simultaneous bonding can include taurine, amino acids, polyamino compounds such as polyethyleneimine functional materials, etc. in the separation and purification of benzoic acid compounds and oligosaccharide samples in traditional Chinese medicine extracts, wherein the traditional Chinese medicine can be one or more of traditional Chinese medicines and foods such as astragalus, rehmannia, and codonopsis.